PROTESTANTIZEM VČERAJ, DANES IN JUTRI. Ur. Franc Kuzmič, Polonca Šek Mertük: Petanjci, Murska Sobota, Ljubljana: Ustanova dr. Šiftarjeva fundacija, Slovensko protestantsko društvo Primož Trubar, Znanstvenoraziskovalni center SAZU, Prekmurska [Pomurska] akademsko znanstvena unija (PAZU), 2015. 391 str. - Šek Mertük, Polonca (Slavia Centralis, 2020)
The paper presents the collection Protestantizem včeraj, danes in jutri (Protestantism Yesterday, Today and Tomorrow), which is the result of a two-day international symposium taking place on 16 and 17 October 2014 in Radenci.
Keywords: Slovene language; protestantism; history of language; sociology; art; review